2014
DOI: 10.1097/scs.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Facial Soft-Tissue Morphology of Adolescent Patients With Nonsyndromic Bilateral Cleft Lip and Palate

Abstract: The purpose of this study was to cephalometrically evaluate the facial soft-tissue characteristics of adolescent patients with bilateral cleft lip and palate (BCLP) and to compare them with a noncleft control group. Lateral cephalometric radiographs obtained from 56 adolescents with nonsyndromic BCLP (29 boys and 27 girls) were analyzed and compared with 67 control subjects (29 boys and 38 girls) who were matched for sex, age, and ethnicity. All patients had been operated on before the age of 2 years for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Thinner subnasale thickness was also reported by Liu et al, 12 who investigated the soft-tissue morphology of the patients affected by unilateral CLP. Hasanzadeh et al 18 reported that the male patients with BCLP had statistically significantly thinner subnasale thickness, and the female patients had thinner subnasale and thicker labrale inferius values compared with the controls. The differences between our findings and those of Hasanzadeh et al might be due to several factors, including different film techniques used in the studies, and the distribution of the ages and the study samples.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Thinner subnasale thickness was also reported by Liu et al, 12 who investigated the soft-tissue morphology of the patients affected by unilateral CLP. Hasanzadeh et al 18 reported that the male patients with BCLP had statistically significantly thinner subnasale thickness, and the female patients had thinner subnasale and thicker labrale inferius values compared with the controls. The differences between our findings and those of Hasanzadeh et al might be due to several factors, including different film techniques used in the studies, and the distribution of the ages and the study samples.…”
Section: Discussionmentioning
confidence: 97%
“…Few studies have reported on the hard-tissue and soft-tissue morphologies of patients affected by unilateral CLP. 8,9,14,15 Only 1 study, by Hasanzadeh et al, 18 gave information about facial soft-tissue morphology. According to that unique study, the BCLP patients differed from the control subjects by having a flatter facial profile, a thinner and retruded nasal base, a flatter nasal tip, and a reduced upper lip length.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1 High incidence rates of this anomaly were reported for Asian populations (0.079%-0.374%), intermediate rates for whites (0.091%-0.269%), and low rates for the African populations (0.018%-0.167%). 2 CLP usually leads to various functional disturbances, including problems with feeding, hearing, speech, respiratory system, and dentofacial development [3][4][5][6] ; thus, its treatment requires a multidisciplinary team approach with good interaction between different specialties such as speech therapy, otolaryngology, psychology, audiology, pedodontics, orthodontics, prosthodontics, and plastic and maxillofacial surgery. 7 Previous studies have shown that patients affected by CLP usually have anterior and posterior crossbite, midface deficiency with a tendency toward a Class III malocclusion, increased vertical dimensions, and decreased pharyngeal airway volume.…”
Section: Introductionmentioning
confidence: 99%